Seizures in HIV: The case for special consideration - DOHERTY, COLIN; Zaporojan, Lilia; McNamara, Patricia H.; Williams, Jennifer A.; Bergin, Colm; Redmond, Janice (My University, 2018)
Purpose: This study aimed to determine the rate, cause and management of seizures in the context of potential ART–ASD interactions in a cohort of HIV + individuals. Methods: Records of 604 HIV + patients were reviewed and those reporting epilepsy/seizure diagnosis were further evaluated. Results: This cohort exhibited a seizure rate of 2.4%. HIV + patients treated for epilepsy displayed low serum ASD levels and failed to achieve seizure control. They were more likely to disengage from Neurology follow-up. Conclusion: For HIV + patients presenting with seizures/epilepsy the ASD prescription and the provision of supplementary support services needs to be carefully considered.
Keywords: HIV; Seizure; Epilepsy; ASD-ART interaction